Allometric estimation of tree biomass through a generalized approach at species and multispecies level - Paz Pellat, Fernando; Salas Aguilar, Víctor; Velázquez Rodríguez, Alma; Sánchez Sánchez, Cristóbal (Instituto de Ecología, A.C., 2021)
The total aboveground biomass (B) of terrestrial ecosystems has carbon stocks of high importance for mitigation actions of climate chan¬ge through mechanisms such as REDD+. To be able to access possible financial compensation to avoid deforestation or degradation of forests, in addition to conservation, increase of stocks and sustainable forest management, it is necessary to evaluate biomass and carbon estimation errors, which are generally associated with the allometric model used. The common allometric models, relationships between normal diameter (D) and total height (H) with biomass, use statistical techniques that do not take advantage of the relations between the exponents of the models, nor the relationships between the constants and exponents of each model. This work presents a generalized theoretical framework applicable at the level of monospecies and multispecies, which is applied to a set of 684 measurements of D, H and B, from 23 databases of individual species. The results obtained, when all the parameters were available, were practically without error. In the cases of lack of information of a parameter, the estimations made under different approximations showed estimation errors comparable with those obtained by the classical methods of development of generalized allometric models. The methodological process presented serves as the basis for the proposal of changes in the allometric information generation approaches, to simplify and reduce errors in estimating biomass and carbon.